Elements of Bioeconomy - Biernat, Krzysztof (IntechOpen, 2019)
This book is a review of the basic problems associated with the implementation of bioeconomic processes. The book contains chapters developed by teams from different countries of the world and therefore the chapters correspond to the degree of advancement of the areas within the bioeconomy in these countries. In selected areas, basic concepts and selected technological processes that create this area of the economy to ensure sustainable development have been characterized.